Analysis of Associative Meaning in The Mini Album Song Kalah Bertaruh by Nadin Amizah - Yuyun Setiawati; Udjang Pairin M.Basir (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
The rapid development of language not only has an impact on its use but also has an impact on changes in the meaning of words. Therefore, currently changes in meaning appear in various types, one of which is associative meaning. Associative meaning is defined as the meaning of a word that correlates with the context outside the language. Associative meaning consists of connotative meaning, stylistic meaning, effective meaning, collocative meaning and reflective meaning. This research aims to reveal whether or not there is associative meaning in the songs contained in the mini album lose bets by Nadin Amizah, this is also the research data used in this research using documentation type data collection techniques as well as reading and note taking. The results of the analysis concluded that the mini album losing bets by Nadin Amizah contained 23 data with associative meanings. The types of associative meaning include 9 data containing connotative meaning which is also interpreted as figurative meaning, 3 data containing collocative meaning because they relate to a word that was born from another word in the same context, 6 data containing stylisti meaning because they relate to the style of word choice. or social differences, 1 data contains a reflective meaning because it causes an automatic reaction so that it forms another meaning and the last is an effective meaning of 1 data because it reflects emotions related to something that is heard or discussed. The researcher then described these data using qualitative descriptive research.